The Relationship Between Diabetes Mellitus and Cancers and Its Underlying Mechanisms - Zhu, Bing; Qu, Shen (Frontiers in Endocrinology, 2022)
Epidemiological studies suggest associations between diabetes mellitus and some cancers. The risk of a number of cancers appears to be increased in diabetes mellitus. On the other hand, some cancer and cancer therapies could lead to diabetes mellitus. Genetic factors, obesity, inflammation, oxidative stress, hyperglycemia, hyperinsulinemia, cancer therapies, insulin and some oral hypoglycemic drugs appear to play a role in the crosstalk between diabetes mellitus and cancers. This review summarized the associations between various types of diabetes and cancers and updated available evidence of underlying mechanisms between diabetes and cancers.